Penerapan Pembelajaran Berdiferensiasi Berbasis Proyek Dalam Implementasi Kurikulum Merdeka pada Pembelajaran Bahasa Arab - Ma’wa, Auladatil; Suparmanto; Abdurrahman, Azmy; Najwa, Dewi Qotrun Nada; Karim, Syauqi Miftahul (Yayasan Daarul Qimmah Gorontalo, 2023)
Phenomena in Arabic language teaching found in the field show students' difficulties in understanding and applying Arabic language interpretations. One of the reasons for this is that the learning provided does not pay attention to each student's abilities, so it does not provide learning according to the needs of each student. This learning difficulty is also caused by monotonous learning, which causes students to lack interest and motivation in learning Arabic. Purpose: The aim of this research is to analyze the application of project-based differentiated learning in the implementation of the independent curriculum in Arabic language learning at MTs NW Mercapada. Method: The research uses descriptive qualitative methods. Results and Discussion: By implementing project-based differentiated learning in this research, it shows positive results in increasing students' understanding of mufrodat in Arabic language learning at MTs NW Mercapada